Organic–inorganic hybrid nanocomposite for enhanced photo-sensing of PFO-DBT:MEH-PPV:PC71BM blend-based photodetector - Zafar, Q.; Najeeb, M.A.; Ahmad, Z.; Sulaiman, Khaulah (Kluwer (now part of Springer), 2015)
The sensing parameters of previously reported PFO-DBT:MEH-PPV:PC71BM ternary blend-based organic photodetector have been improved in the present study. Improvement has been successfully demonstrated by doping TiO2 nanoparticles in the PEDOT:PSS thin film. TiO2 nanoparticles of 50, 100 and 250 nm diameters have initially been dispersed in PEDOT:PSS, and the resulting suspension has been spun coated on glass substrates and subjected to UV/vis and PL study. Thin film of PEDOT:PSS–TiO2 (100 nm) has shown maximum quenching in PL spectra, along with fairly good visible-light absorption. For further studies, 5 wt% TiO2 (100 nm) nanoparticles dispersion in PEDOT:PSS has been utilized for the fabrication of ITO/PEDOT:PSS–TiO2/PFO-DBT:MEH-PPV:PC71BM/Al photodiode. The PEDOT:PSS–TiO2 suspension has been spun coated onto the ITO substrates primarily and annealed to densify the film by vaporizing water contents in the film. A ternary blend of PFO-DBT:MEH-PPV:PC71BM in optimized volumetric ratio has been sequentially spun-cast to serve as a photoactive film. Significantly improved values of the sensing parameters such as responsivity (4 mA/W) and photo-to-dark current ratio (~6.4 × 104) have also been found. Response/recovery times of the fabricated sensor remain almost the same (<1 s) as previously reported for PFO-DBT:MEH-PPV:PC71BM ternary blend.